Efeito in vitro do haloperidol e risperidona na ativação inflamatória de macrófagos RAW 264.7 - Jung, Ivo Emilio da Cruz (2015)
Introduction: Antipsychotic drugs, such as haloperidol (typical) and risperidone (atypical) increase the risk of obesity and other endocrine disturbs in psychiatric patients when used in long term treatments. There is some evidence that suggest that the proinflammatory effect of these drugs could contribute to the stablishement of these morbidities. However, the results obtained until now are contradictory. For this reason, investigaions using isolated cells from the immune system that are directly involved with inflammatory procecesss are considered relevant. Objective: The present study investigated the in vitro effect of three haloperidol and risperidone concentrations (20, 30 e 40 μM) on RAW 264.7 cell line macrophages for analysis of morphologicl pattern, oxide nitric levels, cell viability (24, 48 and 72 h), apoptosis induction and cytokine production. Methods: Macrophage cell culture was made in RPMI 1640 medium, 10% fetal bovine serum, 1% antibiotics in CO2 % incubator at 37oC. The nitric oxide (NO) levels were determined by Griess assay modified to measure nitrite/nitrate ratio by spectrophotometry. Apoptosis was determined by flow cytometry using Annexin V and iodide propidium as cell markers. Gene expression analysis of Bcl-2 and BAX genes were performed by QT-PCR was well as quantification of caspases 8 and 3 levels were performed by ELISA immunoassay. Treatments were compared by One-way analysis of variance followed by Tukey or Dunnet post hoc test. Results: Macrophages exposed to different concentrations of haloperidol and risperidone presented increased NO levels, morphological alterations as well as decrease in viability after 24, 48 and 72 h of exposition. The apoptosis level of cells was significantly higher than untreated cells when macrophages were exposed to haloperidol (40μM) and all treatments with risperidone after 24 h exposition. Bcl-2/BAX ratio gene expression was downregulated in cells exposed to haloperidol and risperidone confirming apoptosis induction by these drugs. Caspases 8 and 3 levels also increased in a dose-depend way. The inflammatory cytokine levels increased in all treatments (IL-1β, IL- 6,TNFα, INFγ) whereas IL-10 levels, a antiinflammatory cytokine decreased. Conclusion: The whole of results suggest that haloperidol and risperidone act directly on macrophages and can exacerbate inflammatory processes. The inflammatory mechanism of these actions can influence the development of obesity in patients that make long term use of these drugs.